(untitled) (Research, Society and Development, 2022)
Early childhood education is considered one of the most important stages in the formation of children, in this context daycare centers have a fundamental role because they serve children from 0 to 3 years old, and are of paramount importance for the development of the little ones. This report aims to reflect on the importance of daycare for the development of children aged 0 to 3 years from the experience of pedagogy academics. This is a descriptive study, of the experience report type, carried out from the student experience in curricular internships of the pedagogy course. In the classroom it was observed that specific knowledge was absorbed by the children, some children arrived without speaking and during the classes there was already an improvement in social communication between them, gross motor coordination also improved a lot, they also arrived without any kind of independence , that is, totally dependent on their parents, many could not go to the bathroom alone and many were in diapers, and many of them no longer use them, and almost 20% of the room is still in the process. The concrete and real factors that were observed and pointed out in the present work demonstrate that the earlier the child starts in day care, there is an improvement in the ease of their learning, making them obtain an educational background, since it is from the kindergarten that life begins. of student of the child will initiate.